The spectral evolution of cool white dwarfs. Issue Volume 15:Issue S357(2019) (October 2019) - Blouin, Simon; Dufour, Patrick
Abstract: Empirically characterizing the spectral evolution of cool white dwarfs is a prerequisite to understanding the physical processes that shape the evolution of these old objects. However, the high photospheric densities of cool helium-rich atmospheres seriously complicate the study of those stars. We have recently developed an updated atmosphere code that is appropriate for high densities and that can model any cool white dwarf (including DZs and DQpecs). Here, we present recent advances in our understanding of the spectral evolution of cool white dwarfs that were made possible thanks to these improved models. We discuss in particular the evolution of the hydrogen-rich to helium-rich ratio at low effective temperatures as well as the DQ→ DQpec transition.